UJI KELAYAKAN MEDIA PEMBELAJARAN VIDEOSCRIBE BERBASIS ANIMATION DRAWING MENGGUNAKAN MODEL ADDIE PADA MATERI PENCEMARAN LINGKUNGAN - Aini, Kamilatul; Rosidi, Irsad; Muharrami, Laila Khamsatul; Hidayati, Yunin; Wulandari, Ana Yuniasti Retno (Natural Science Education Research, 2023)
The purpose of this research to develop animated video videoscribe based animation drawing as a science learning media, media development videoscribe based on this animation drawing focus on the material environmental pollution class Vll smp/mts, development design used is the ADDIE model (Analyze, Design, Develop, Implement, dan Evaluate). The subjects of this study were 19 students. The research instruments used were the media validity sheets, the material experts, and the student response questionnaires. Based on research results, it can be concluded that: (1) The average percentage of validator 1 and validator 2 is validity of media experts was 93% with very valid criteria and 98% reliability with reliable criteria. The average percentage of validator 1 and validator 2 is validity of material experts was 95.75% with very valid criteria and 98% reliability with reliable criteria, so that the animation drawing-based Videoscribe media is suitable for used by students in learning with environmental pollution material.